PENERAPAN BALANCED SCORECARD DALAM PENGUKURAN KINERJA ORGANISASI PUBLIK (Studi Kasus Pada Badan Pendapatan Daerah Kabupaten Mojokerto) - Fajriah, Lailatul; Hidayat, M. Taufiq (Universitas 17 Agustus 1945 Surabaya, 2019)
ABSTRACTThis study aims to analyze the performance of the Mojokerto Regency Revenue Agency with the Balanced Scorecard approach. Performance is measured through four perspectives: financial perspective, customer perspective, internal business process perspective and learning and growth perspective. This type of research is a descriptive qualitative research with a case study approach. The data used are primary data from interviews and secondary data from documentation. Data analysis was performed by covering four perspectives, the financial perspective was measured by the value for money method, the perspective of the customer with the customer satisfaction index. Internal business process perspective is measured by service cycle efficiency and learning and growth perspective with employee satisfaction index. The results of this study indicate that evaluating performance from a financial perspective is economical, efficient and effective. Performance from the customer's perspective is good, because taxpayers are satisfied with the services provided by the Mojokerto Regency Revenue Agency. The internal business process performance is classified as efficient in providing services, and the assessment of learning and growth perspective performance is good, because employees of the Mojokerto Regency Revenue Agency are satisfied with what is provided by the Mojokerto Regency Revenue Agency. Keywords: Balanced Scorecard, Public Organizations